The effect of project aid fragmentation on economic growth. Issue 2 (17th February 2020) - Furukawa, Mitsuaki
ABSTRACT: Aid fragmentation has been examined as a negative phenomenon to development outcomes based on aid volumes. However, aid fragmentation is a situation in which a large number of fragmented and non-coordinated donor projects carried out using procedures that vary from donor to donor are introduced in a recipient country, raising the transaction costs. Therefore, this article examines the effect of aid fragmentation based on the number of projects. It confirms that project aid concentration increases economic growth in poor countries with a higher degree of aid dependence. Under the SDGs, it is expected that aid fragmentation will become a more pressing concern.